The potential neuroprotective role of carboxyhemoglobin (COHb) against hemorrhagic stroke - Fernandes, Tatiana Pereira (2024)
Stroke is the leading cause of death in Portugal and a major global cause of permanent neurological disability. Although hemorrhagic stroke accounts for just 15% of all stroke cases, it poses a higher risk of mortality by triggering harmful biological processes, including oxidative stress, increased neuroinflammation, neuronal damage and blood-brain barrier (BBB) dysfunction. Cell-free hemoglobin (Hb), released after the rupture of red blood cells, is easily oxidized into pro -oxidant forms like methemoglobin (MetHb) that further contribute to these harmful processes. Addressing the harmful effects of pro-oxidant MetHb represents a potential therapeutic strategy for hemorrhagic stroke. Carbon monoxide (CO), a gas endogenously produced by the stress-response enzyme heme-oxygenase, has been shown to have cytoprotective, anti-inflammatory, antioxidant, and anti-apoptotic effects. This gas binds to reduced Hb with high affinity forming carboxyhemoglobin (COHb), which is traditionally considered a marker of CO toxicity. However, recent studies have suggested that COHb may have a neuroprotective role by stabilizing Hb in its reduced state and preventing the formation of toxic heme byproducts. The goal of this study was to evaluate the potential protective effects of COHb against cell-free Hb toxicity by assessing its effects in microglia, neurons, and endothelial cells, focusing on neuroinflammation, cell viability, and BBB integrity. The results showed that while both COHb and MetHb induced oxidative stress, COHb led to significantly lower levels of reactive oxygen species (ROS) production and neuroinflammation in microglia compared to MetHb. However, COHb did not show a cytoprotective effect on neuronal viability compared to MetHb. In terms of BBB integrity, the results were inconclusive, suggesting the need for further investigation into COHb's protective mechanisms. Overall, these findings highlight the therapeutic potential of COHb in treating hemorrhagic stroke by mitigating the damaging effects of cell-free Hb. Nevertheless, additional research is necessary to better understand its neuroprotective and anti-neuroinflammatory mechanisms and its impact on preserving BBB integrity.